Developing Game-Based Learning Model of Long Jump for Elementary School - Sari, Zihan Novita (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2019)
This research aims was to develop a product of a game-based learning model of long jump for elementary school students. This research is a development research using Research and Development from Borg and Gall which consists of ten stages. The subject in this research is elementary school student in Palembang city. Data were collected through documentation, observation, interview and learning test of long jump skills. Data analysis was done descriptively, qualitatively and quantitatively. The results of the study prove that: 1) the development of game-based learning model of long jump for elementary school students has been declared valid, 2) game-based learning model of long jump for elementary school is  80% can increase the ability of long jump and build a sense of courage and give motivation to elementary school students